A study on the factors influence employee satisfaction towards safety at the workplace / Alia Syafiqa Mohamad Rozali and Wan Nor Ain Wan Ibrahim - Mohamad Rozali, Alia Syafiqa; Wan Ibrahim, Wan Nor Ain (2018)
The purpose of the study is to identify factor influencing employee satisfaction towards safety at workplace. This study was conducted in Universiti Teknologi Mara (UiTM) Cawangan Kedah as the researchers have identified an issue regarding safety in this institution. According to a local newspaper, Utusan Malaysia, it is reported there was an accident which had caused casualty of an employee of this institution. It is reported that the employee fell from the ceiling on the fourth floor of the building while doing the cleaning work at the building. The researchers are decided to measure the employee satisfaction using quantitative method as safety will provide a sense of security and satisfaction to employees. This study is conducted by focusing on non-academic employee in UniversitiTeknologi Mara (UiTM) Cawangan Kedah because the non-academic employees have more engagement to workplace safety. The number of respondents is 155 for data collection using the sample size formula table proposed by Sekaran and Bougie (2003). The methodologies used are descriptive analysis, correlation and multiple regressions for test analysis. The result from the analysis shows that there are significant relationship of dependant variable which is employee satisfaction and impendent variable namely supervisor's role, safety practice and working condition. The result of the analysis also shows the most influential factor influence employee satisfaction towards safety at workplace is supervisor's role.